The Effect of Lyso-PAF on Ciliary Activity of Human Paranasal Sinus Mucosa in vitro - T. Ganbo; K. Hisamatsu; H. Inoue; T. Nakajima; Y. Murakami (Mediators of Inflammation)
The effect of lyso-PAF on ciliated cells was investigated in vitro. Normal mucosa was surgically obtained from human paranasal sinuses and incubated in the form of tissue culture. Ciliated epithelium was magnified under an inverted microscope, and ciliary movement was photo-electrically measured. Ciliary activity was significantly inhibited by 10−8 M lyso-PAF and could be restored. The effect of lyso-PAF was completely blocked by CV-6209, a specific PAF antagonist. The PAF concentration in the incubation medium of lyso-PAF was determined by radioimmunoassay, because PAF is a well known inhibitor of ciliary activity. PAF gradually increased and after 20 min reached its maximal level. These findings indicated the existence of an enzyme in the paranasal sinus mucosa, by which lyso-PAF is converted to PAF, and that lyso-PAF can inhibit ciliary activity by means of PAF.